PENGARUH KEPEMIMPINAN, MOTIVASI, KESEJAHTERAAN, DAN KEDISIPLINAN TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN KRADENAN KABUPATEN GROBOGAN - -, Siswojo -; Widajanti, Erni - (Universitas Slamet Riyadi, 2010)
ABSTRACT The reaching of target of organization do not only depend on modern equipments, complete facilities and basic facilities, but exactly more depend on human being working the therefore, needed a human resource which with quality that is officer working its and can give result of good job and also have the high performance to support the duties at work nya utilize to reach the maximal result and target in line with local government. Basically organizational efficacy as a whole is contribution from result work all side do not aside from countryside peripheral in Kecamatan Kradenan of Kabupaten Grobogan. High Officer Performance is not an coincidence without executing something action meaning, but many factor influencing among others motivate and upheld discipline. Keywords: leadership, motivate the, prosperity, discipline and performance of government officer countryside.